1985
DOI: 10.1042/bj2250375
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferases of human brain. Evidence for two immunologically distinct types of 26500-Mr subunits

Abstract: Human brain contains one cationic (pI8.3) and two anionic (pI5.5 and 4.6) forms of glutathione S-transferase. The cationic form (pI8.3) and the less-anionic form (pI5.5) do not correspond to any of the glutathione S-transferases previously characterized in human tissues. Both of these forms are dimers of 26500-Mr subunits; however, immunological and catalytic properties indicate that these two enzyme forms are different from each other. The cationic form (pI8.3) cross-reacts with antibodies raised against cati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…It was also reported that one cationic and two anionic forms of soluble GSTs were distinguished in the human brain by isoelectric focusing (40). Consistent with these reports, DE-52 chromatography revealed the existence of four GST isoenzymes in the rat cerebellum (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…It was also reported that one cationic and two anionic forms of soluble GSTs were distinguished in the human brain by isoelectric focusing (40). Consistent with these reports, DE-52 chromatography revealed the existence of four GST isoenzymes in the rat cerebellum (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…TRIzol Ò Reagent, dNTP, ribonuclease inhibitor, M-MLV reverse transcriptase, Taq polymerase were from Invitrogen, proteinase K was from ICN, oligo(dT) 15 primer was from Promega. Reagents for polyacrylamide gel electrophoresis were from Bio-Rad, rabbit anti-human GST-pi polyclonal antibody was from Novocastra, standard GST pi from human placenta from Sigma, ECL plus Western Blotting Detection System from Amersham.…”
Section: Methodsmentioning
confidence: 99%
“…In humans, eight gene families of GST have been characterized for isoforms pi, mu, alpha, theta, zeta, sigma, kappa and chi (12)(13)(14). GST pi, mu and alpha are present in human central nervous system (15,16). The main isoform present in human brain is GST pi (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GST activity-GSTs have been grouped into species-independent classes of isozymes, including both cytosolic and microsomal enzymes (Morgenstern et al, 1979;Mannervik, 1985). Three families of cytosolic soluble GSTs, α (GSTA), μ (GSTM), and π (GSTP), were known in the brain (Theodore et al, 1985;Board et al, 1990). Cayman's GST assay kit measured total GST activity (cytosolic and microsomal) using 1-chloro-2,4-dinitrobenzene (CDNB) as the substrate.…”
Section: Enzyme Activity Assaysmentioning
confidence: 99%